Spanish as a Language of Scientific Communications: Santiago Ramón y Cajal and Bernardo Houssay’s Considerations - Von Stecher, Pablo (MEDICA REVIEW. International Medical Humanities Review / Revista Internacional de Humanidades Médicas, 2019)
Over the course of a wide range of written work, the Argentine physician Bernardo Houssay (1947 Nobel Prize in Physiology) vindicated the contributions of the Spanish anatomist Santiago Ramón y Cajal (1906 Nobel Prize in Medicine) and the way his research contributed to dismiss prejudices against Spanish scientific activity. The object of this article is to inquire into Cajal and Houssay’s considerations about scientific communications (conferences, articles, university lectures) in Spanish and about Spanish as the language of science. In a corpus of documents written by both figures, there have been analyzed representations and linguistic ideologies, namely, representations that refer and evaluate linguistic objects (in our case, “Spanish language” and “scientific discourse”) and their articulations with specific cultural, political or social formations (Arnoux and Del Valle 2010). Thus, inquiries are made on descriptive and prescriptive statements that define characteristics and style of scientific communications and ideologemes (Angenot 2010) on which argumentations are supported. The analysis notices criticism to the Spanish-speaking articulation characterized by hyperbolic rhetoric, alien to the criteria of precision and strictness typical of scientific discourse; as well as it reveals gestures or interventions that, in different degrees, tried to vindicate or encourage the use of Spanish in scientific activity.